New developments in categorical data analysis for the social and behavioral sciences - Ark, L. Andries van der; Croon, Marcel A.; Sijtsma, K. (Klaas), 1955- (Quantitative methodology series., 2005)
A collection of studies on modern categorical data analysis methods, emphasizing their application to relevant and interesting datasets. A prominent breakthrough in categorical data analysis is the development and use of latent variable models.